Manajemen Pembinaan Atlet Bulutangkis Kota Surakarta (Survei Terkait Persiapan Pekan Olahraga Provinsi Jawa Tengah 2026) - Revina Nuri Wardani; Agus Supriyoko; Danang Adhi Kusuma (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The aims of this research are (1) To find out the selection process for badminton athletes in Surakarta City, (2) To find out the training program implemented, (3) To find out the role of coaches, administrators and parents, (4) To find out the facilities and infrastructure, (5) To find out the level of technical, physical and mental readiness, (6) To find out government or sponsor support, (7) To find out the obstacles faced, and (8) To find out the evaluation and follow-up carried out. Data collection was carried out with collect data in study this is observation, interviews, documentation and questionnaires for coaches, management, organizations and athletes. The approach used in study This is a mixed method, namely research that aims for get an overview of something current and current situation​​​ ongoing as well as centered on actual problems.​ Data collection was carried out with collect data in study this is observation, interviews, documentation and questionnaires for coaches, management, organizations and athletes. The study involved 10 subjects, with the collected data analyzed using descriptive statistical techniques presented in the form of percentages and interview results. Based on the results of the analysis of the management of each questionnaire and interview with coaches, management, organizations and athletes, it was obtained that (1) The selection process for badminton athletes for the 2026 Central Java Provincial Games was carried out internally and fell into the "very good" category, (2) The training program implemented was running well and fell into the "very good" category, (3) The role of coaches, administrators and parents in improving athlete performance was running well and there was mutual communication, (4) Facilities and infrastructure in coaching were fulfilled by management, (5) The level of technical, physical and mental readiness of athletes had met the criteria desired by coaches, (6) The government (KONI) or sponsors supported the coaching of badminton in Surakarta City in facing the 2026 Central Java Provincial Games, (7) There were several obstacles faced in the athlete coaching process, (8) Evaluations were held periodically at least once every two weeks and follow-up was carried out after each stage of athlete coaching.